Identifying the Potential Differentially Expressed miRNAs and mRNAs in Osteonecrosis of the Femoral Head Based on Integrated Analysis - Hao Y (Dove Medical Press, 2021)
Yangquan Hao, Chao Lu, Baogang Zhang, Zhaochen Xu, Hao Guo, Gaokui Zhang Department of Osteonecrosis and Joint Reconstruction, Honghui Hospital Xian Jiao Tong University Health Science Center, Xian, Shaanxi 710068, People’s Republic of ChinaCorrespondence: Yangquan HaoDepartment of Osteonecrosis and Joint Reconstruction, Honghui Hospital Xian Jiao Tong University Health Science Center, No. 555 Youyi East Road, Xian, Shaanxi 710068, People’s Republic of ChinaTel +86 13991038599Fax +86 29-87894724Email yangquan_haodoctor@163.comPurpose: Osteonecrosis of the femoral head is a common disease of the hip that leads to severe pain or joint disability. We aimed to identify potential differentially expressed miRNAs and mRNAs in osteonecrosis of the femoral head.Methods: The data of miRNA and mRNA were firstly downloaded from the database. Secondly, the regulatory network of miRNAs–mRNAs was constructed, followed by function annotation of mRNAs. Thirdly, an in vitro experiment was applied to validate the expression of miRNAs and targeted mRNAs. Finally, GSE123568 dataset was used for electronic validation and diagnostic analysis of targeted mRNAs.Results: Several regulatory interaction pairs between miRNA and mRNAs were identified, such as hsa-miR-378c-WNT3A/DACT1/CSF1, hsa-let-7a-5p-RCAN2/IL9R, hsa-miR-28-5p-RELA, hsa-miR-3200-5p-RELN, and hsa-miR-532-5p-CLDN18/CLDN10. Interestingly, CLDN10, CLDN18, CSF1, DACT1, IL9R, RCAN2, RELN, and WNT3A had the diagnostic value for osteonecrosis of the femoral head. Wnt signaling pathway (involved WNT3A), chemokine signaling pathway (involved RELA), focal adhesion and ECM-receptor interaction (involved RELN), cell adhesion molecules (CAMs) (involved CLDN18 and CLDN10), cytokine–cytokine receptor interaction, and hematopoietic cell lineage (involved CSF1 and IL9R) were identified.Conclusion: The identified differentially expressed miRNAs and mRNAs may be involved in the pathology of osteonecrosis of the femoral head.Keywords: osteonecrosis of the femoral head, miRNAs, mRNAs, signaling pathway